Building Script of Jump Scare Scene in Indonesian Horror Box Office Film “KKN Di Desa Penari” - Nurazizah, Laila; Mukhtiaranto, Iryulandi (ULTIMART Jurnal Komunikasi Visual, 2023)
A jump scare is a technique used in horror films that aims to surprise the audience by using a sudden change of image, loud sound, or both for generating powerful simulated fear experiences in films. “KKN di Desa Penari” is a film that has been watched by over 10 million viewers in cinemas. This film contains believable real-event content-wise based on threads written on Social Media that goes viral. This study aims to investigate how “KKN di Desa Penari”'s script builds jump scare scenes in film and creates fears that are needed as a great experience for viewers. This study describes scene components in script and mise-en-scene that elevates viewers' expression on jump scare by conducting analysis from the original script and film “KKN di Desa Penari”. In conclusion, this study shows that the script for the jump scare scene in this film is not only about sudden immediate shocks and jump scares but also in terms of building a sense of fear in the script using components in scene design, which are turning points, setup/payoff, emotional dynamics, natural choice. Keywords: jump scare; horror; film; kkn di desa penari; script.